Constraining the Date of the Martian Dynamo Shutdown by Means of Crater Magnetization Signatures. Issue 11 (11th November 2017) - Vervelidou, Foteini; Lesur, Vincent; Grott, Matthias; Morschhauser, Achim; Lillis, Robert J.
Abstract: Mars is believed to have possessed a dynamo that ceased operating approximately 4 Ga ago, although the exact time is still under debate. The scope of this study is to constrain the possible timing of its cessation by studying the magnetization signatures of craters. The study uses the latest available model of the lithospheric magnetic field of Mars, which is based on Mars Global Surveyor data. We tackle the problem of nonuniqueness that characterizes the inversion of magnetic field data for the magnetization by inferring only the visible part of the magnetization, that is, the part of the magnetization that gives rise to the observed magnetic field. Further on, we demonstrate that a zero visible magnetization is a valid proxy for the entire magnetization being zero under the assumption of a magnetization distribution of induced geometry. This assumption holds for craters whose thermoremanent magnetization has not been significantly altered since its acquisition. Our results show that the dynamo shut off after the impacts that created the Acidalia and SE Elysium basins and before the crust within the Utopia basin cooled below its magnetic blocking temperature. Accounting for the age uncertainties in the dating of these craters, we estimate that the dynamo shut off at an N (300) crater retention age of 2.5–3.2 or an absolute model age of 4.12–4.14 Ga. Moreover, the Martian dynamo may have been weaker in its early stage, which if true implies that the driving mechanism of the Martian dynamo was not the same throughout its history. Plain Language Summary: Mars is believed to have possessed a dynamo that ceased operating approximately 4 Ga ago, although the exact time is still under debate. The scope of this study is to constrain the possible timing of its cessation by studying the magnetization signatures of craters. The study uses the latest available model of the lithospheric magnetic field of Mars, which is based on Mars Global Surveyor data. Since the complete magnetization cannot be uniquely recovered by magnetic field measurements, we infer the visible part of the magnetization, that is, the part of the magnetization that gives rise to the observed magnetic field. Further on, we demonstrate that a zero visible magnetization is a valid proxy for craters whose thermoremanent magnetization has not been significantly altered since its acquisition. Our results show that the dynamo shut off after the impacts that created the Acidalia and SE Elysium basins and before the crust within the Utopia basin cooled down. Accounting for the age uncertainties in the dating of these craters, we estimate that the dynamo shut off at an absolute model age of 4.12–4.14 Ga. Moreover, the Martian dynamo may have been weaker in its early stage, which if true implies that that the driving mechanism of the Martian dynamo was not the same throughout its history. Key Points: A visible magnetization model of Mars is obtained up to SH degree and order 110 A zero visible magnetization is shown to be a valid proxy for a crater's entire magnetization being zero in the absence of major alterations The Martian dynamo ceased during the Noachian era